Optimization of Highly Porous Mannitol Preparation using Ammonium bicarbonate and Citric acid as Templating Agents with Spray Drying Technique - Kusumorini, Nindya; Adhyatmika (Journal of Food and Pharmaceutical Sciences, 2023)
This study investigated the effect of ammonium bicarbonate and citric acid as templating agents using spray drying technique to improve the porosity of D-mannitol powder. It has been shown that textural properties, such as surface area and pore volume produced, are affected by the type and concentration of templating agents, inlet temperature, and outlet temperature of spray drying. The structure of mannitol powder produced changes considerably due to the change in its textural properties to particle powder with high porosity, surface area, and pore volume. The results show that the ratio of D-mannitol to ammonium bicarbonate 10:5 w/w% with water solvent temperature of 30 oC, spray drying inlet temperature of 120 oC, and spray drying outlet temperature of 70 oC, resulting in the highest porosity, surface area, and pore volume. The surface area of mannitol increased from 1.167 m2/g to 3.571 m2/g, followed by an increase in pore volume from 0.0022 cc/g to 0.012 cc/g and pore diameter from 75.33 Å to 115.2 Å. The scanning electron microscope (SEM) results are consistent with the surface area measurement results using the Surface Area Analyzer (SAA). The resulting spray-dried mannitol powder with a high specific surface area allows it to be used as an excipient in solid formulations of oral preparations.